Competitiveness Factors of Enterprises: A Survey Research in Peripheral Regions, Poland - Małgorzata JUCHNIEWICZ (Communications of International Proceedings, 2022)
The aim of the research was to identify the most important factors of competitiveness of enterprises in peripheral regions of north-eastern Poland (in the poviats: Bartoszyce, Braniewo, Ketrzyn and Lidzbark Warminski). The void in literature makes this study important. The author's own research was carried out by the method of a diagnostic survey with the use of a questionnaire. The examined entities were characterized by a significant own (endogenous) potential, consolidated by the experience, skills and knowledge of the owners. The place of residence was the most common motivation to start a business activity by the surveyed entrepreneurs. A significant awareness of entrepreneurs was identified, recognizing the need to strengthen the pro-quality approach in production and services. There was a desire to increase production capacity by focusing on the development of material elements of production systems - preferring the purchase of machinery and equipment with possible access to financial resources. The surveyed companies need, among others: preparation of individual competitive strategies and greater involvement in various activities and institutional relations aiming at searching for and implementing innovative strategies, greater involvement in cooperation with the business environment - non-governmental organizations, consulting films, agricultural advisory centers, clusters economic, etc., implementation of advanced management techniques at the microeconomic level, simplification of organizational structures, wider use of IT systems supporting decisions, continuous improvement of effectiveness based on cost optimization, pro-innovative activities.
Keywords: the competitiveness of enterprises; peripheral regions; regional development.